Review of damage mechanism and protection of aero-engine blades based on impact properties. (October 2022) - Yang, Pingping; Yue, Wenhui; Li, Jian; Bin, Guangfu; Li, Chao
Highlights: Impactors are classified into sand, metal, bird and ice according to their properties. Impact type, shape and size have a significant impact on damage pattern. The damage caused by metal and birds to the blade is more obvious. Studying blade damage mechanisms is critical to blade design and protection. The lack of research on blade impact damage is found and its trend is put forward. Abstract: During the service of the aircraft, the engine blades are inevitably damaged by the impact of foreign objects with different properties such as sand particles, which seriously affects the safety of the aircraft and even leads to such serious accidents as air crashes. Aiming at four foreign objects including sand, metal, birds and ice, this paper summarizes the damage mechanism of the blade from the aspects of the impactor's size, hardness and shape, analyzes the advantages and disadvantages of the test methods and summarizes different ways to protect against of foreign object damage (FOD). The development trend of aero-engine blade damage is prospected from the aspects of multi-factor coupled damage mechanism analysis, experimental equivalence principle, and damage prediction using deep learning and big data technology.